2018
DOI: 10.1038/s41598-018-26165-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Moisture Content for Congou Black Tea Withering Leaves Using Image Features and Nonlinear Method

Abstract: Withering is the first step in the processing of congou black tea. With respect to the deficiency of traditional water content detection methods, a machine vision based NDT (Non Destructive Testing) method was established to detect the moisture content of withered leaves. First, according to the time sequences using computer visual system collected visible light images of tea leaf surfaces, and color and texture characteristics are extracted through the spatial changes of colors. Then quantitative prediction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…In tea, the metabolites can help the tea plants resist abiotic and biotic stresses and ensure the quality of tea [23][24][25][26]. Metabolomics can identify and quantify the metabolites, metabolic pathways and regulatory mechanisms [27,28], and has been widely used in tea research, including to screen fine tea, for tea quality evaluation [29][30][31], to understand how cultivation conditions induce physiological changes [32,33], to study the metabolism of non-biological and biological stress reactions, and to outline the metabolic pathways [34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In tea, the metabolites can help the tea plants resist abiotic and biotic stresses and ensure the quality of tea [23][24][25][26]. Metabolomics can identify and quantify the metabolites, metabolic pathways and regulatory mechanisms [27,28], and has been widely used in tea research, including to screen fine tea, for tea quality evaluation [29][30][31], to understand how cultivation conditions induce physiological changes [32,33], to study the metabolism of non-biological and biological stress reactions, and to outline the metabolic pathways [34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…e annual consumption of tea may reach about 2.5 million metric tons (processed leaves), 75% of which is black tea [1]. Congou black tea is a unique variety of Chinese black tea, which is made with careful skill to produce thin, tight strips without breaking the leaves [2]. e tea processing includes withering, rolling, fermenting, and drying.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation as a key step that can enhance the activation level of enzymes, promote the oxidative condensation of polyphenols, and produce a strong fragrance, thus forming the special desirable color and avor of black tea ready for drying and packaging. e nal drying will assure that the leaves will produce the expected dark color and strong fragrance when "brewed" with boiling water [2,3]. e content of thea avins is the most important evaluation index of the quality of Congou black tea.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical changes during withering are influenced by duration of withering and environmental conditions like air temperature, relative humidity, air flow rate etc. In recent days studies have been reported to correlate degree of withering with textural properties, color of leaves, or machine vision-based image analysis (Liang et al, 2018;Ye et al, 2019;Yu et al, 2019). and aroma of black tea.…”
Section: Novelty Impact Statementmentioning
confidence: 99%